Comparative evaluation of instant 'poundo' cocoyam (Colocasia esculenta) and yam (Dioscorea rotundata) flours produced by flash and cabinet drying. (21st July 2020) - Adeboyejo, Folasade Olabimpe; Aderibigbe, Olaide Ruth; Obarayi, Monsurat Titilope; Sturm, Barbara
Summary: Cocoyam, an important staple crop especially among the low‐income earners in tropical regions of the world, is highly underutilised for industrial applications. This study investigates the nutritional, colour and rheological properties of instant flours ('poundo') from two cultivars of Colocasia esculenta (white‐NCe010 and purple‐NCe003) and Dioscorea rotundata (var. Oginni), and sensory attributes of doughs prepared from reconstituted flours. Tubers were processed into instant flours using cabinet and flash drying methods. Significant differences ( P  < 0.05) in the proximate and mineral composition and pasting properties of flours were found. Sensory panellists rated reconstituted poundo yam (8.17–8.20) and white cocoyam (7.50–7.95) higher than purple cocoyam (6.60–7.10) meals. Influence of drying method on sensory characteristics of flours was not significant. Instant poundo cocoyam and yam flours could serve as novel convenience and ready‐to‐eat food products which could contribute to increasing the commercial and industrial application options for these underutilised tubers beyond their present basic use. Abstract : Instant yam and cocoyam flours made from cabinet and flash drying methods were investigated for their nutritional, colour, rheological and sensory attributes. Varietal difference was more critical than drying methods to produce instant poundo flours with desirable quality attributes